2016
DOI: 10.1039/c6cp00365f
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity of the doubly charged [8]circulenes

Abstract: Magnetically induced current densities and current pathways have been calculated for a series of fully annelated dicationic and dianionic tetraphenylenes, which are also named [8]circulenes. The gauge including magnetically induced current (GIMIC) method has been employed for calculating the current density susceptibilities. The aromatic character and current pathways are deduced from the calculated current density susceptibilities showing that the neutral [8]circulenes have two concentric pathways with aromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 81 publications
3
59
0
Order By: Relevance
“…We have also noted this occurrence of what we are somewhat colloquially calling 'the triplet ground-state problem' in some charged species of a hypothetical conjugated system (structure 3, on the left-hand side of Figure 2) and in the case of an extant hydrocarbon of the [8]-circulene family (structure 4, on the right-hand side of Figure 2), the latter of which was recently considered by Baryshikov et al [32] These two structures will be used in this presentation, along with structures 1 and 2 (in Figure 1), in order to illustrate the observations that are being documented here about the 'triplet ground-state problem'.…”
mentioning
confidence: 52%
“…We have also noted this occurrence of what we are somewhat colloquially calling 'the triplet ground-state problem' in some charged species of a hypothetical conjugated system (structure 3, on the left-hand side of Figure 2) and in the case of an extant hydrocarbon of the [8]-circulene family (structure 4, on the right-hand side of Figure 2), the latter of which was recently considered by Baryshikov et al [32] These two structures will be used in this presentation, along with structures 1 and 2 (in Figure 1), in order to illustrate the observations that are being documented here about the 'triplet ground-state problem'.…”
mentioning
confidence: 52%
“…Our quantum chemical calculations at the GIAO/ B3LYP/6-311+G(d,p) level of theory confirmed the antiaromatic character of the inner eight-membered ring of quasicirculenes 40 and 42 ± 46 based on the positive values of NICS(0) and NICS(1). 118 We also found that the aromaticity of dithienothiophene quasicirculenes strongly depends on the positions of the sulfur atoms in the annulated moiety. The strict alternation of single and double bonds in the series of quasicirculenes 45, 46 and 40 containing the odd number of thiophene moieties makes it impossible to predict the existence of the corresponding quasicirculenes containing an even number of thiophene rings.…”
Section: Structures 40 ± 46mentioning
confidence: 96%
“…Neutral [8]circulenes have two concentric current pathways. The inner octatetraene core (the hub) sustains a paratropic ring current and along the outer edge of the macrocycle (the rim) flows a diatropic ring current of the same size . Neutral [8]circulenes are globally nonaromatic.…”
Section: Applicationsmentioning
confidence: 99%